Reading the Tourist Destination: Bibliotourism and Place Perception - Roque, Maria Isabel; Guerreiro, Dália (Journal of Tourism, Sustainability and Well-being, 2021)
Bibliotourism is a recent concept and an emergent segment of cultural tourism. Considering both the phenomena of tourism increase and the passage from the information society on to the knowledge society, the role of public and heritage library faces new challenges and priorities. The building’s architecture, the artistic bookshelves display, and the value of the collection may be offered as cultural values, determining the library as a tourist attraction. Furthermore, libraries may also assist in all the travel phases, from the preparation to the place experience and its memory preservation. Considering that the cultural tourism motivations are related to learning, experiencing and understanding the place’s history, culture and heritage in both intangible and tangible components, libraries, as documental repositories, are crucial to support the tourist’s information needs and demands. While traditional libraries are reinventing cultural mediation strategies to spread knowledge about those issues, namely by organising exhibitions and performative events, digital libraries, over the past two decades, have become crucial channels in obtaining information. By providing access to data through a range of resources and services in a very inclusive and ubiquitous manner, digital libraries are an essential tool to the tourism planners and consumers, and play a strategic role for the newest tourist generations, and mainly for the Generation Z tourists. Bibliotourism and tourism activities focused on libraries create mutual benefits and development opportunities, as the available knowledge enhances the sense of place and more immersive experiences. The research in this field is at a very early stage, and the theoretical framework is underdeveloped, even if some case studies have been presented in the last years. The main objectives of this paper, conceived as a descriptive study, are to provide critical analysis of the bibliotourism concept and to provide an overview of how to approach the public libraries functions from a touristic perspective. The methods used to achieve these objectives are based on bibliographic research, by confronting the term citations in the general and specialised press with its references in scientific journals, followed by the direct observation of the use of libraries by tourists, in the framework of a theoretical and empirical research model. The expected results are the creation of a new perspective about integrating libraries, cultural mediation and entertainment in leisure tourism and a contribution to the definition and description of a bibliotourism concept.